Adult Congenital Heart Disease Patients Experience Similar Symptoms of Disease Activity. (March 2016) - Cedars, Ari M.; Stefanescu Schmidt, Ada; Broberg, Craig; Zaidi, Ali; Opotowsky, Alexander; Grewal, Jasmine; Kay, Joseph; Bhatt, Ami B.; Novak, Eric; Spertus, John
Abstract : Background—: There is a lack of objective data on the symptoms characterizing disease activity among adults with congenital heart disease (ACHD). The purpose of this study was to elicit the most important symptoms from patients across the spectrum of ACHD and to examine whether reported symptoms were similar across the spectrum of ACHD as a foundation for creating a patient-reported outcome measure(s). Methods and Results—: We constructed a 39-item survey using input from physicians specializing in ACHD to assess the symptoms patients associate with disease activity. Patients (n=124) prospectively completed this survey, and the results were analyzed based on underlying anatomy and disease complexity. A confirmatory cohort of patients (n=40) was then recruited prospectively to confirm the validity of the initial data. When grouped based on underlying anatomy, significant differences in disease-related symptom rankings were found for only 6 of 39 symptoms. Six symptoms were identified which were of particular significance to patients, regardless of underlying anatomy. Patients with anatomy of great complexity experienced greater overall symptom severity than those with anatomy of low or moderate complexity, attributable exclusively to higher ranking of 5 symptoms. The second patient cohort had symptom experiences similar to those of the initial cohort, differing in only 5 of 39 symptoms. Conclusions—: This study identified 6 symptoms relevant to patients across the spectrum of ACHD and remarkable homogeneity of patient experience, suggesting that a single disease-specific patient-reported outcome can be created for quality and outcome assessments.